2015
DOI: 10.30552/ejihpe.v5i3.139
|View full text |Cite
|
Sign up to set email alerts
|

Impulsividad y consumo de alcohol y tabaco en adolescentes

Abstract: La etapa de la adolescencia se caracteriza por una prematura experimentación de nuevas experiencias y sensaciones. Estas experiencias, pasan en ocasiones por el consumo de drogas, que aun siendo legales y socialmente aceptadas, las consecuencias negativas en el desarrollo del adolescente comienzan a hacerse patentes. En los últimos años se ha observado una disminución en el consumo de tabaco en los adolescentes españoles, no así en el consumo de alcohol. Una de las causas de inicio en las drogas es la personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
17

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
0
8
0
17
Order By: Relevance
“…Revista de Educación, 360, 533-556. Barragán, A.B., Martos, A., Cardila, F., Molero, M.M., Pérez-Fuentes, M.C., y Gázquez, J.J. (2015). Variables relacionadas y prevalencia del burnout en profesionales sanitarios.…”
Section: Referenciasunclassified
See 2 more Smart Citations
“…Revista de Educación, 360, 533-556. Barragán, A.B., Martos, A., Cardila, F., Molero, M.M., Pérez-Fuentes, M.C., y Gázquez, J.J. (2015). Variables relacionadas y prevalencia del burnout en profesionales sanitarios.…”
Section: Referenciasunclassified
“…Uno de los objetivos fundamentales del sistema educativo es la transmisión de conocimientos al alumnado. Así, asegurar que esta transmisión se produzca en las mejores condiciones posibles es un reto para la sociedad actual, especialmente teniendo en cuenta la alta tasa de abandono entre los estudiantes de todos los niveles educativos, siendo necesario para ello conocer los factores individuales que influyen en este proceso (Borzone, 2017;Guido et al, 2014;Parra y Pérez, 2010;Pérez-Fuentes et al, 2015;Quevedo-Blasco, Quevedo-Blasco, y Téllez, 2016).…”
unclassified
See 1 more Smart Citation
“…These relationships could be particularly apparent during adolescence when changes in development occur, and at the same time, more opportunities for substance use appear [22,23]. A study by Pérez-Fuentes et al [24] analyzing the relationship between impulsivity and use of alcohol and tobacco by adolescents contained data suggesting that students who say they are users have significantly higher scores on impulsivity. Charles et al [25] found that higher levels of impulsivity and sensation-seeking become more evident in early adolescence and are predictors of higher substance use in midadolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data shows that alcohol, tobacco and cannabis are the most used drugs among US (National Institute on Drug Abuse, 2015) and European adolescents (European Commission, 2012; European Monitoring Centre for Drugs and Drug Addiction, 2012;Pérez-Fuentes et al, 2015;Steketee, Jonkman, Berten, & Vettenburg, 2013). Among secondary students in Spain, a national survey indicates that rates of frequent alcohol, tobacco and cannabis use are 74%, 29.7% and 16.1%, respectively (Plan Nacional sobre Drogas, 2014).…”
mentioning
confidence: 99%